Principles of Auditing and Other Assurance Services - Whittington O.Ray (McGraw -Hill, 2007)
Whittington/Pany’s Principles of Auditing, is a market leader in the auditing discipline. Until October 2002, Ray Whittington was a member of the Audit Standards Board and prior to Ray being on the ASB, Kurt Pany was on the board. Whittington is currently President of the Auditing Section of the American Accounting Association. Principles of Auditing presents concepts clearly and proactively monitors changes in auditing making the relationship between accounting and auditing understandable. The 16th edition maintains the organization and balance sheet orientation, while adding and enhancing topics of Risk, Assurance Services, Fraud, E-Commerce, and the latest auditing standards to meet the needs of the current marketplace.